COGNITIVE FEATURES OF MANAGERIAL DECISION MAKING IN TERMS OF THE DIGITAL ECONOMY. THE RESULTS OF EXPERIMENT - V. V. Degtyareva; D. A. Sozaeva (Вестник университета, 2019)
The transformation of managerial decision-making processes in the digital economy, the modification of the boundaries of the personal space of an employee and manager (manager) when making collegial decisions through social networks and other modern communication tools have been investigated. The problems of assessing the quality of such decisions, the ways and tools of their elimination have been considered. The information base of the article were Russian and foreign researches in the field of management theory and practice, personal observations of the authors, as well as the results of the experiment, conducted by the authors. Such methods of scientific research as analysis, synthesis, generalization, experiment have been used.